Pengalaman Perawat Dalam Merawat Pasien Perilaku Kekerasan Yang Disebabkan Halusinasi Di Ruang Melati Rsj Dr. Radjiman Wediodiningrat Lawang - Sulistyono Sulistyono; Indah Winarni; Heni Dwi Windarwati (Akademi Keperawatan Dharma Husada Kediri, 2014)
The high numbers of patients with an angry expression of asertif with a history of violent behavior that average caused hallucinations, need to get attention and serious handling for all parties concerned especially the nurse on duty in rsj dr. Radjiman wediodiningrat lawang. This is because the patients in acute conditions as mentioned above. may harm or threaten the safety of the patient or the safety of others. Research purposes which is to dig experience nurse in giving an orphanage nursing in patients behavior violence caused hallucinations in melati room rsj dr. Radjiman wediodiningrat lawang. The method of this research is to use qualitative research designs with descriptive phenomenology of approach. Participants who participated in this research as many as four people room nurse melati rsj dr. Radjiman wediodiningrat lawang. The result of analisi with the methods colaizzi against the transcript verbatim produce three themes the steps the preformance of the process of nursing, self-awareness, and empathy. A conclusion that obtained from the results of this research is a nurse in to treating a patient behavior violence caused hallucinations there has been a cycle is turning which is that of self- awareness, empathy, and carry out steps in the process of nursing. The institution clinic should increase the capability of perawatnya especially in treating patients in the condition of acute or crisis Key words: patients with violent behavior, nurse experience, qualitative